Penerapan model e-learning berbasis website kalase dalam meningkatkan hasil belajar media pembelajaran pada mahasiswa Pendidikan Teknologi Pertanian - Nurmila Nurmila; Lahming Lahming (Seminar Nasional LP2M UNM, 2019)
Kalase website-based e-learning distribution model aims to determine the strategies for implementing E-Learning-based models in the subject of Learning Media in the Agricultural Technology Education Study Program, Faculty of Engineering, Makassar State University. This study aims to find out the student learning outcomes by applying the E-Learing model based on the Kelase Website on Learning Media in the Agricultural Technology Education Study Program Faculty of Engineering, Makassar State University. The method used in data collection is by conducting observations, tests and producing descriptive data. The results achieved in this study are the increase in learning outcomes for Grade 02 students in the Agricultural Technology education program at the Faculty of Engineering, Makassar State University, on the subject of learning media.